Kemampuan Guru Sosiologi Dalam Melaksanakan Kompetensi Pedagogik Di SMA Muhammadiyah 1 Pontianak - Maulana, Agus (Jurnal Pendidikan Sosiologi dan Humaniora, 2017)
The title of this Tesis is "The Ability Of Sosiology"™s Teacher In Doing Pedagogic Competence At Sma Muhammadiyah 1 Pontianak". General problem of this research in is "How is the ability of Sosiologys"™s Teacher in doing pedagogic competence at SMA Muhammadiyah 1 Pontianak?" The objectives of this research are to analyse the ability of Sosiology"™s teacher in developing curriculum and to analyse the ability of Sosiology"™s teacher in designing Learning activies at SMA Muhammadiyah 1 Pontianak. The approach that used in this research is qualitative approach with decriptive method.   The technic of data collecting chosen are observation, interview, and documentation technic.Keywords: Teacher"™s Ability, Learning Process, Pedagogyc Competence.